Classification of Determinants of Burnout Syndrome in Terms of Personality Traits of Public Administration Managers - Eva Brijová; Veronika Mlynárová; Peter Mlynár; Zuzana Birknerová; Ivan Uher (Social Sciences, 2022)
Burnout syndrome is considered a disease of modern societies. Research has shown that burnout is related to reduced performance in the workplace. Many times, burnout syndrome occurs in helping professions, such as healthcare or social services. The aim of this explanatory research is to determine the relationship between the degree of burnout syndrome, personality traits, and determinants of burnout syndrome of managers in public administration. The Maslach Burnout Inventory (MBI) has been used to measure burnout syndrome. Personality traits, i.e., neuroticism, extraversion, openness to experience, five-factor inverters (NEO FFI), and assessing the determinants of burnout syndrome (PDSV) have been considered. The research sample consisted of (n = 226) managers in public administration. Based on the determined three hypotheses, we brought together sufficient evidence to provide more than a tentative conclusion that there is a positive association between NEO FFI and PDSV, MBI and PDSV, as well as MBI and NEO FFI. It can be inferred that a high workload and a lack of resources are some of the most compelling aspects that can instigate burnout. In addition to what has been assumed, there is argumentation among professionals about what is burnout, its symptoms, diagnostic criteria, environment of its occurrence, which demands further investigation to waive the vagueness and ambiguity of the concept of burnout syndrome.